Study of impact of vertical integration in medical education in a medical college of India - Singh, Arun; Katyal, Rashmi; Chandra, Shalini; Joshi, Hari S.; Singh, Kashmir (International Journal Of Community Medicine And Public Health, 2017)
Background: It is postulated that memory of basic sciences in medical curriculum and its correlation with clinical work among undergraduate students is less than expected, which drives into the dire necessity to vertically integrate the subjects. The aims and objectives of the study were to assess the impact of vertical integration of teaching among medical undergraduate students of a medical college and to assess the perceptions of the medical undergraduate students about the vertical integration of teaching during lecture classes in a medical college. Methods: Ninety six out of 119 second MBBS students had undergone vertically integrated sessions by six departments of a medical institute on assessment and management of diarrhoea using four interactive methods and two traditional teaching methods during April 2015 to September 2015 among the M.B.B.S. students of Rohilkhand Medical College and Hospital, Bareilly. Inclusion criteria were all the M.B.B.S. 2nd year students of 2013 batch were included in the study. Exclusion criteria were the M.B.B.S. students who were absent on the day of study were excluded. Competency of students was assessed using competency based assessment methods i.e. OSCE, OSPE, DOPS, SAQ and MCQs and their perceptions recorded using Likert’s Scale. Comparative analysis of pre and post-tests was done using paired t-test and ANOVA. Results: The difference between the mean value of the marks obtained by the medical students using the five assessment tools was found to be statistically significant (p value being <0.05) using paired t-test, showing improvement in competency. Vertical integration was strongly agreed upon as the best method by 45.8% on Likert scale. Comparative analysis of variance (ANOVA) of the assessment tools was also found to be highly significant (p value being <0.05). Conclusions: The indexed study derives us to a conclusion to incorporate vertical integration in our medical education in order to accomplish higher learning domains.